Testicular metastasis from urothelial carcinoma: case report and literature review - Liu, Changxue; Liu, Jing; Yang, Qingbo; Song, Leilei; Ma, Xiaocheng; Wang, Yonghua (Frontiers in Oncology, 2024)
Urothelial carcinoma with testicular metastasis is extremely rare, and its mode of metastasis, prognosis, and treatment are unclear. In this report, we present an extraordinarily rare case of testicular metastasis arising from urothelial carcinoma eight years after surgery. The patient underwent left orchiepididymectomy and received immunotherapy postoperatively. After a 6-month follow-up, there were no signs of recurrence. Moreover, the clinical characteristics, metastasis pattern and treatment plan were also summarized based on 14 earlier reported cases of urothelial carcinoma with testicular metastasis.